Photoprotective and Antioxidant Potential of Indonesia’s Klanceng Honey Beehive Waste - Yuliana Purwaningsih; Ahmad Fuad Masduqi; Erwin Indriyanti; Mighfar Syukur (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2023)
A byproduct of the honey processing called Klanceng honey beehive waste is said to still contain secondary metabolites that are beneficial to health. The objective of this research was to assess the photoprotective properties of an ethanol extract, n-hexane fraction, and ethyl acetate fraction obtained from the waste of an Indonesian Klanceng honey beehive that originated in Magelang. The DPPH free radical technique was applied to quantify antioxidant properties, and the Mansur equation’s SPF value was used to calculate photoprotective activity. The analysis of the data revealed that the IC50 values for the ethanol extract, n-hexane fraction, and ethyl acetate fraction were, respectively, 470.2935±0.9249, 207.1869± 2.6510, and 216.4892±0.8349. The ethanol extract, n-hexane fraction, and ethyl acetate fraction of the samples had SPF values of 3.872, 3.529, and 9.358, respectively. The ethyl acetate fraction, as opposed to the ethanol extract and the n-hexane fraction, has greater potential as a photoprotective agent as a result.